PENYELENGGARAAN KURSUS PRA NIKAH DI KABUPATEN PURWAKARTA: KASUS KUA PURWAKARTA, CIBATU, DAN BABAKAN CIKAO: IMPLEMENTATION OF PRE-MARRIAGE COURSE IN PURWAKARTA: A CASE STUDY OF RELIGIOUS AFFAIRS OFFICES (KUA) PURWAKARTA, CIBATU, AND BABAKAN CIKAO - Daniel Rabitha (Balai Penelitian dan Pengembangan Agama Jakarta, 2015)
This paper presents the results of research on the implementation of pre-marriage course in Purwakarta. There are three Religious Affairs Offices (KUA) that are used as research subjects, namely Religious Affairs Office district of Purwakarta, Cibatu, and Babakan Cikao. Data are generated from interviews with key informants and field observation. Implementation of pre-marriage course on three Religious Affairs Offices broadly refers to Directorat General Rules No. DJ.II/491/2009. The implementation of pre-marriage course is generally carried out according to the capability of Religious Affairs Offices. The effectuation models for either groups or individuals are carried out in accordance with the wedding process and the willingness of the bride and groom. The speakers of the course frequently come from the Religious Affairs Office, while the material presented is concerning with the issues of government regulations related to marriage, marriage law, and reminding offer and acceptance-ijab kabul process, which will be carried out during wedding procession, and duration of the implementation as a group approximately 3 hours and an individual approximately 1 hour. Broadly speaking, the implementation of pre-marriage course has embraced the principles of public service (UU No. 25/2009). However, it has not been done professionally because funding owned by Religious Affairs Office is lacking.Keywords: Pre-marriage courses, public services, Religious Affairs Offices, Purwakarta. Tulisan ini menyajikan hasil penelitian tentang penyelenggaraan Kursus Pra Nikah pada Kabupaten Purwakarta. Ada tiga Kantor Urusan Agama (KUA) yang dijadikan subjek penelitian, yakni KUA Kecamatan Purwakarta, Cibatu, dan Babakan Cikao. Pengumpulan data penelitian ini dihasilkan dari wawancara dengan informan kunci dan observasi lapangan. Penyelenggaraan Kursus Pra Nikah pada ketiga KUA secara garis besar mengacu pada Perdirjen No. DJ.II/491/2009. Penyelenggaraan Kursus Pra Nikah secara umum dilakukan sesuai kemampuan dari KUA. Model penyelenggaraan, baik secara kelompok maupun dengan perorangan dilakukan sesuai dengan peristiwa nikah dan kesediaan calon pengantin. Narasumber lebih sering berasal dari pihak KUA, materi yang disampaikan menyangkut masalah peraturan pemerintah terkait perkawinan, hukum pernikahan, perihal berumah tangga, dan pengingatan kembali proses ijab qabul yang nanti akan dilakukan catin saat melakukan prosesi pernikahan, dan durasi penyelenggaraan secara kelompok kurang lebih 3 jam dan perorangan 1 jam. Secara garis besar, penyelenggaraan Kursus Pra Nikah sudah menganut asas pelayanan publik (UU No. 25/2009), hanya saja pada asas profesional belum bisa dipenuhi karena berbenturan dengan pendanaan yang dimiliki KUA.Kata Kunci: Kursus Pra Nikah, pelayanan publik, Kantor Urusan Agama, Purwakarta.